Stem Cells Regenerating the Craniofacial Skeleton: Current State-Of-The-Art and Future Directions - Oliver, Jeremie D. (J Clin Med, 2020)
The craniofacial region comprises the most complex and intricate anatomical structures in the human body. As a result of developmental defects, traumatic injury, or neoplastic tissue formation, the functional and aesthetic intricacies of the face and cranium are often disrupted. While reconstructive techniques have long been innovated in this field, there are crucial limitations to the surgical restoration of craniomaxillofacial form and function. Fortunately, the rise of regenerative medicine and surgery has expanded the possibilities for patients affected with hard and soft tissue deficits, allowing for the controlled engineering and regeneration of patient-specific defects. In particular, stem cell therapy has emerged in recent years as an adjuvant treatment for the targeted regeneration of craniomaxillofacial structures. This review outlines the current state of the art in stem cell therapies utilized for the engineered restoration and regeneration of skeletal defects in the craniofacial region.